(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2011)
Key words: CKD (Chronic Kidney Disease); DM (Diabetes mellitus); HTN (Hypertension); BMI (Body Mass Index); C-G (Cockcroft-Gault) formula; MDRD (Modification of Diet in Renal Disease) equation DOI: 10.3329/jcmcta.v21i2.7733 Journal of Chittagong Medical College Teachers’ Association 2010: 21(2):25-29